OPTIMALISASI PERAWATAN SEKOCI (LIFEBOAT) DIATAS KAPAL MV. GLOVIS DAYLIGHT UNTUK KESELAMATAN AWAK KAPAL DALAM KEADAAN EMERGENCY - Ahmad, Zulfikar; Putra Yuda, Anak Agung Ngurah Ade Dwi; Dahri, Muh.; Haryanto, Tri (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
When a ship is sailing, undesirable events often occur. This can be caused by natural factors or human error. To reduce the risk of accidents during these adverse events, ships must be equipped with safety equipment that can be deployed quickly in the event of an emergency. Additionally, training crew members in the use of safety equipment and maintenance of safety equipment is the most important action that must be taken to prepare the entire crew for an emergency. The aim of this research is to determine the implementation of maintenance and training procedures for ship lifeboats which must comply with SOLAS (Safety of Life at Sea). When this research was carried out, an accident occurred on the MV ship. Glovis Daylight which caused one of the ship's crew to be sent home. The author used an intensive method by joining a ship for 12 months. Descriptive qualitative research methods were used in this research. Data collection methods were obtained from the author's own experience, daily notes on board the ship, interviews with the ship's crew, direct observation.